The Sociolinguistics of Higher Education Language Policy and Internationalisation in Catalonia - Soler, Josep; Gallego-Balsà, Lídia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book investigates the sociolinguistic dimension of the internationalisation of higher education, examining the linguistic tensions and ambiguities experienced by universities around the world, particularly in non-anglophone contexts. Joining current debates within discursive and ethnographic approaches to language policy, the authors analyse the narrative emerging from university language policy documents, and then trace the stance-taking processes of different stakeholders at a small university in Catalonia. They pay particular attention to how teachers, administrative staff, and exchange students position themselves in connection to the role of Catalan and its coexistence with other languages at the university. This book will be of interest to language policy scholars and practitioners, as well as graduate students in sociolinguistics and applied linguistics Josep Soler is Assistant Professor of Applied Linguistics at the Department of English, Stockholm University, Sweden. His main research interests cover the areas of language policy and linguistic ideologies; he has recently focused on the role of English in the internationalisation of higher education, and on the study of practices and ideologies in multilingual families. Lídia Gallego-Balsà is a Post-doctoral Researcher and Lecturer at the Department of English and Linguistics at the University of Lleida, Spain. Her interests include multilingualism, language policy, internationalisation, interculturality, discourse analysis, and ethnography.
Chapter 1: Introduction: Language policy and the internationalisation of higher education in Catalonia -- Chapter 2: Language policy, internationalisation, and multilingual higher education: An overview -- Chapter 3: Language policy regulations at Catalan universities: A content analysis of their narrative -- Chapter 4: Clashing stances towards Catalan: An ethnographic study in a small university in Catalonia -- Chapter 5: The internationalisation of Catalan universities: Multilevel language policies, circulating discourses, and stakeholders' stance-taking -- Chapter 6: Conclusions.
Keywords: Sociolinguistics; Language policy; Anthropological linguistics; Applied linguistics; Education, Higher; Sociolinguistics; Language Policy and Planning; Linguistic Anthropology; Applied Linguistics; Higher Education